2017
DOI: 10.2147/copd.s137872
|View full text |Cite
|
Sign up to set email alerts
|

Identification and distribution of COPD phenotypes in clinical practice according to Spanish COPD Guidelines: the FENEPOC study

Abstract: BackgroundThe Spanish Guidelines for COPD (GesEPOC) describe four clinical phenotypes: non-exacerbator (NE), asthma-COPD overlap syndrome (ACO), frequent exacerbator with emphysema (EE), and exacerbator with chronic bronchitis (ECB). The objective of this study was to determine the frequency of COPD phenotypes, their clinical characteristics, and the availability of diagnostic tools to classify COPD phenotypes in clinical practice.Materials and methodsThis study was an epidemiological, cross-sectional, and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 36 publications
11
45
0
4
Order By: Relevance
“…In our study, the non-exacerbator phenotype was the most common with a prevalence of 46.7% followed by exacerbator with chronic bronchitis (22.4%), exacerbator with emphysema (16.4%), and ACOS (14.5%). These percentages are similar to 47.5%, 29.1%, 17.0%, and 6.5%, respectively, found in a cross-sectional sample of 647 patients with COPD reported in the study of Calle Rubio et al, 20 in which the same GesEPOC guidelines for the definition of the four phenotypes were used. Also, our results are consistent with the distribution of phenotypes found in 4,508 audited clinical records of patients diagnosed with COPD reported in the EPOCONSUL study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the non-exacerbator phenotype was the most common with a prevalence of 46.7% followed by exacerbator with chronic bronchitis (22.4%), exacerbator with emphysema (16.4%), and ACOS (14.5%). These percentages are similar to 47.5%, 29.1%, 17.0%, and 6.5%, respectively, found in a cross-sectional sample of 647 patients with COPD reported in the study of Calle Rubio et al, 20 in which the same GesEPOC guidelines for the definition of the four phenotypes were used. Also, our results are consistent with the distribution of phenotypes found in 4,508 audited clinical records of patients diagnosed with COPD reported in the EPOCONSUL study.…”
Section: Discussionsupporting
confidence: 86%
“… 19 The lower percentage of exacerbators with chronic bronchitis among patients recruited at pulmonology services than in primary care centers (15.3% vs 32%) might be explained in part by a more intense therapy in patients followed by pulmonology specialists. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The Spanish Guidelines for COPD (GesEPOC) describe four clinical phenotypes. The ‘exacerbator with emphysema phenotype’ is an important one of the four clinical phenotypes 17. The objective of this study was to evaluate the relationship between serum biomarkers level and severity of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a heterogeneous disease and it is currently believed that the same phenotype may have similar clinical outcomes and therapeutic responses. According to the Spanish COPD phenotype classification,17 the ‘exacerbator with emphysema phenotype’ is a phenotype of the common phenotype of COPD with poor prognosis and poor treatment response. Therefore, the aim of this paper was to investigate the biomarkers levels of FKN, NE andMMP-12 in COPD ‘exacerbator with emphysema phenotype’ and to evaluate the associations between biomarkers levels and the severity of disease by spirometric measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to asthma, pathogenic mechanisms in COPD are associated with a greater extent with Th1, Th17, ILC1, and ILC3 cells as well as with neutrophils; similarly, clustering on clinical features for COPD that may help to specify management and provide a prognostic outcome is lacking, as no universal consensus regarding their definition and prevalence exists. Clinically, many COPD phenotypes and subtypes of COPD exacerbations have been described; however, clustering across COPD cohorts revealed that the COPD heterogeneity is better characterized by continuous disease traits coexisting in varying degrees within the same individual, rather than by mutually exclusive COPD subtypes …”
Section: Phenotypes Endotypes and Biomarkers In Asthma And Copd: Unmentioning
confidence: 99%